2020
DOI: 10.3390/cells9071695
|View full text |Cite
|
Sign up to set email alerts
|

CD47 Promotes Age-Associated Deterioration in Angiogenesis, Blood Flow and Glucose Homeostasis

Abstract: The aged population is currently at its highest level in human history and is expected to increase further in the coming years. In humans, aging is accompanied by impaired angiogenesis, diminished blood flow and altered metabolism, among others. A cellular mechanism that impinges upon these manifestations of aging can be a suitable target for therapeutic intervention. Here we identify cell surface receptor CD47 as a novel age-sensitive driver of vascular and metabolic dysfunction. With the natural aging proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 61 publications
1
47
1
Order By: Relevance
“…They display comparable structural features that consist of well-defined binding domains that link to proteoglycans and integrins [ 4 , 5 ]. Thrombospondins have diverse physiological and pathophysiological tissue-specific actions that include effects on vascular responsiveness [ 6 , 7 ] and angiogenesis [ 8 , 9 , 10 ], platelet activation [ 11 , 12 ], inflammation [ 13 , 14 ], and cell death [ 15 ] that directly impact on wound healing and tumorigenesis.…”
Section: Thrombospondin-1 (Tsp1)mentioning
confidence: 99%
See 2 more Smart Citations
“…They display comparable structural features that consist of well-defined binding domains that link to proteoglycans and integrins [ 4 , 5 ]. Thrombospondins have diverse physiological and pathophysiological tissue-specific actions that include effects on vascular responsiveness [ 6 , 7 ] and angiogenesis [ 8 , 9 , 10 ], platelet activation [ 11 , 12 ], inflammation [ 13 , 14 ], and cell death [ 15 ] that directly impact on wound healing and tumorigenesis.…”
Section: Thrombospondin-1 (Tsp1)mentioning
confidence: 99%
“…When CD47 expression was absent in human and murine endothelial cells, VEGFR2 phosphorylation was no longer inhibited and angiogenic responses improved [ 10 ]. A recent study revealed that the anti-angiogenic effects of CD47 escalate with age in humans and mice, defining this pathway as a potential therapeutic target in age-associated vascular impairments [ 8 ].…”
Section: Tsp1-cd47 Signalling In Angiogenesis and Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…TSP1 and CD47 are upregulated in aged arteries ( 45 ), and when aortic rings from older individuals were treated with an antibody against CD47, they showed similar sprouting to the aortic rings treated with vascular endothelial growth factor (VEGF). These results revel new and exciting insights into reversing atherosclerosis and the aging process ( 45 ).…”
Section: Tsp1 In Cardiovascular Diseasesmentioning
confidence: 99%
“…As age predisposes the body to insulin resistance and hyperglycemia, CD47 will further inhibit SMCs proliferation and angiogenesis. Indeed, CD47-null aging mice have demonstrated better responses to glucose than control mice ( 45 ).…”
Section: Tsp1 In Glucose Metabolism and Diabetes Mellitusmentioning
confidence: 99%